IOT-BASED LEGAL POLICY IN CO₂ EMISSION SAFETY CONTROL TO SUPPORT GREEN TRANSPORTATION - Hernanda, Trias; Nugroho, Soma Setiawan Ponco; Izzati, Tazkiya Isya; Nisa, Firda Khoirun; Wahyudin, Widya Cholid; Nuriyatman, Eko (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Religious tourism areas in Kudus Regency, Indonesia particularly the Tomb of Sunan Muria and the Tomb of Sunan Kudus are visited by thousands of pilgrims every day, creating significant transportation flows and contributing to air pollution. This study aims to evaluate the environmental quality and legal implications of air pollution caused by transportation activities in these two religious tourism sites. Using an empirical legal research design with a qualitative approach, primary data were collected through interviews and supported by results from Internet of Things (IoT) based air pollution detection devices that measured oxygen (O₂), temperature, and carbon dioxide (CO₂) levels. The results were then analyzed using the mean formula. The findings reveal differing environmental conditions between the two locations. The highland area of Sunan Muria generally shows air quality levels within Indonesia’s permissible standards, while the urban environment of Sunan Kudus records higher CO₂ and temperature levels exceeding the national air pollution threshold. These findings indicate that urban religious tourism faces more severe environmental challenges. The discussion emphasizes the urgent need for legal and policy reform toward a green transportation framework in Kudus Regency. This research contributes to demonstrating how IoT-based monitoring can serve as an empirical foundation for evidence-based environmental policymaking in Indonesia’s tourism sector.